The Effect of Pertlite Nanoparticles on the Tensile Properties of NR/HDPE Composite and Optimization of its Composition Using Response Surface Method - S.M. Aghanejad; J. Ghanbari (Journal of Advanced Materials in Engineering)
In this study, the effect of the perlite nanoparticles on the mechanical properties of a pearlite/NR/HDPE nanocomposite was experimentally investigated. A high-density polyethylene/natural rubber /perlite nanocomposite was synthesized using an internal mixer and a melt mixing method, with varying compositions. Uniaxial tension tests were carried out to obtian the tensile strength and elongation of the samples. The response surface method and the central composite design were employed as experiment design and optimiztion tools to obtian the influence of composite composition parameters, specifically, the weight percentage of perlite and natural rubber. Furthermore, scanning electron microscopy was utilized to inspect the microstructure of the nanocomposite samples, and to evaluate the efficacy of the mixing method. The experimental results derived from the various samples revealed that a sample containing 7 wt.% perlite nanoparticles and 20 wt.% natural rubber demonstrated a significant enhancement in the tensile strength, reaching up to 12 MPa. Moreover, the multivariable optimization data suggested that the optimal weight percentages for natural rubber and perlite nanoparticles were 36.89% and 3.00%, respectively. Under these conditions, both the tensile strength and the elongation at failure point achieved their maximum values, recorded as 8.32 MPa and 38.89%, respectively.